Less Effort, Better Results: How Does Music Act on Prefrontal Cortex in Older Adults during Verbal Encoding? An fNIRS Study - Ferreri, Laura; Bigand, Emmanuel; Perrey, Stephane; Muthalib, Makii; Bard, Patrick; Bugaiska, Aurélia (Frontiers in Human Neuroscience, 2014)
Several neuroimaging studies of cognitive ageing revealed deficits in episodic memory abilities as a result of prefrontal cortex (PFC) limitations. Improving episodic memory performance despite PFC deficits is thus a critical issue in ageing research. Listening to music stimulates cognitive performance in several non-purely musical activities (e.g. language and memory). Thus, music could represent a rich and helpful source during verbal encoding and therefore help subsequent retrieval. Furthermore, such benefit could be reflected in less demand of PFC, which is known to be crucial for encoding processes. This study aimed to investigate whether music may improve episodic memory in older adults while decreasing the PFC activity.Sixteen healthy older adults (µ=64.5y) encoded lists of words presented with or without a musical background while their dorsolateral PFC (DLPFC) activity was monitored using a 8-channel continuous-wave near-infrared spectroscopy (NIRS) system (Oxymon Mk III, Artinis, The Netherlands). Behavioral results indicated a better source memory performance for words encoded with music compared to words encoded with silence (p< .05). Functional NIRS data revealed bilateral decrease of oxyhemoglobin values in the music encoding condition compared to the silence condition (p< .05), suggesting that music modulates the activity of the DLPFC during encoding in a less-demanding direction. Taken together, our results indicate that music can help older adults in memory performances by decreasing their PFC activity. These findings open new perspectives about music as tool for episodic memory rehabilitation on special populations with memory deficits due to frontal lobe damage such as Alzheimer’s patients.